The Effectiveness of Family-Based Digital Interventions on Children’s Anxiety and Quality of Life During Hospitalization - Kurniawati; Dewi Sartika; Samila (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Hospitalization can provoke anxiety and reduced quality of life among children. Family involvement combined with digital media may strengthen coping and create a supportive care experience. Research Objective: This study evaluated the effectiveness of a family-based digital intervention in reducing anxiety and improving quality of life among hospitalized children. Methods: A randomized controlled trial involved 60 children aged 6–12 years in a ward in Makassar. Participants were recruited consecutively and randomly allocated to intervention and control groups. The intervention group received a tablet-based family program for 20–30 minutes twice daily for three days, while the control group received usual care. Anxiety and quality of life were assessed using the STAIC and PedsQL 4.0. Data were analyzed using paired t-tests, independent t-tests, and repeated-measures ANOVA. Results: Anxiety decreased more substantially in the intervention group than in the control group (mean change: −13.90 vs −4.20; p<0.001). Quality-of-life scores increased significantly (16.80 vs 4.90; p<0.001). Significant group-by-time interactions were identified for anxiety and quality of life. Conclusion: Family-based digital interventions effectively reduced anxiety and improved quality of life, supporting their integration into family-centered pediatric nursing care.